Physical, Chemical, and Microbiological Quality Analysis of Home Ice Cubes, Beams, and Crystals in Gang Lebar, Wonocolo, Surabaya - Anisa Shofiyana Azhari; Esti Tyastirin; Hanik Faizah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Ice cubes are complementary products made from frozen water. If ice cubes have been contaminated by chemical compounds or microorganisms, it will cause various health problems. The purpose of this study was to determine the quality of ice cube, block and crystal houses in the Gang Lebar area, Wonocolo, Surabaya. The physical parameters of ice cubes observed were color, smell and taste. The chemical parameters analyzed were Fe and pH. Microbiological parameters were tested by Total Plate Count (TPC), Most Probable Number (MPN), and Salmonella contamination test. The results showed that by observing the physical parameters of the color of the ice cubes, 1 sample of ice cubes was obtained which met the quality requirements of SNI 3839: 2019, namely sample K1, on the physical observation of smell and taste, 1 sample was obtained which did not meet the requirements, namely the ice block sample. Analysis of pH and Fe chemical parameters showed that all samples met the quality requirements of SNI 3839: 2019 in the pH test. Meanwhile, the Fe test of all samples was declared ineligible. Microbiological analysis of ice cubes showed that 1 sample did not meet the requirements. Furthermore, the results of the MPN coliform test stated that 1 sample met the quality requirements with a value of 7 APM/100mL in sample K1. The Salmonella contamination test found 1 positive sample containing Salmonella, namely in the ice block sample.